Molecular analysis of the reactions in Salicornia europaea to varying NaCl concentrations at various stages of development to better exploit its potential as a new crop plant - Fussy, Andre; Papenbrock, Jutta (Frontiers in Plant Science, 2024)
This research directly aligns with the scope of Frontiers in Plant Sciences (Plant Abiotic Stresses) by investigating plant responses to environmental stress factors, specifically salinity. The study employs a multi-disciplinary approach, analyzing gene expression, yield, and metabolites under controlled salinity conditions. Our findings elucidate stress response and protection pathways at the molecular level, including the identification of genes involved in differential stress responses.Furthermore, the research contributes to the development of stress-adapted plants for sustainable agriculture applications, indirectly addressing SDGs 13 (climate action) and 15 (life on land). By analyzing gene expression across various developmental stages and salinity treatments, the study offers valuable insights into the mechanisms underlying tolerance to prolonged salt stress in Salicornia europaea. This knowledge can be instrumental in engineering stress-resistant crops for cultivation in saline environments, promoting sustainable agricultural practices.